Mary Austin's A Woman of Genius: The Text, the Novel and the Problem of Male Publishers and Critics and Female Authors. (Journal of American Culture (01911813))
Mary Austin's feminist novel 'A Woman of Genius' (1912) met with resistance from the male publishing world, and its promotion and critical reception by male critics and booksellers misrepresented and defused much of the book's radical critique of marriage and traditional mores.